1989
DOI: 10.1523/jneurosci.09-03-01018.1989
|View full text |Cite
|
Sign up to set email alerts
|

In vivo development of nicotinic acetylcholine receptor channels in Xenopus myotomal muscle

Abstract: The development of acetylcholine receptor (AChR) channel function in Xenopusmyotomal muscle was studied by singlechannel recordings from cell-attached patches of nonjunctional membrane in viva. AChR channels were studied from the time of their first appearance on the muscle membrane until the time of full maturity of the muscle. Two predominant amplitude classes of AChR channels were observed with slope conductances of about 40 and 60 pS. During the first day after their initial appearance on the membrane, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
25
1

Year Published

1989
1989
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 35 publications
7
25
1
Order By: Relevance
“…Recordings from BC3H-1 cells (27) have not revealed multiple conductance levels of AcChoRs such as we observed in oocytes; however, AcChoR channels with conductances lower than 40 pS have been reported in Xenopus muscle in vivo (7,8,28) and in denervated mouse muscle (29). One of these, a 25-pS channel, has been well characterized in developing Xenopus muscle (8).…”
mentioning
confidence: 42%
See 2 more Smart Citations
“…Recordings from BC3H-1 cells (27) have not revealed multiple conductance levels of AcChoRs such as we observed in oocytes; however, AcChoR channels with conductances lower than 40 pS have been reported in Xenopus muscle in vivo (7,8,28) and in denervated mouse muscle (29). One of these, a 25-pS channel, has been well characterized in developing Xenopus muscle (8).…”
mentioning
confidence: 42%
“…Single channel events were recorded by a List EPC/7 patch clamp amplifier, and stored on FM tape for off-line analysis. The procedures for data analysis were similar to those described (7). Records from a8y3-injected oocytes were low-pass Bessel …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the single-channel level, our results showed that ATP had a selective action on the low-conductance ACh channel, a characteristic only of embryonic muscle cells. Developmental changes of ACh receptor channels have been studied extensively in Xenopus muscle cells in vitro as well as in vivo (Brehm, Kidokoro & Moody-Corbett, 1984;Owens & Kullberg, 1989;Rohrbough & Kidokoro, 1990). Shortly after the initial insertion of ACh receptor channels a great majority of the channels are of an embryonic type (lowconductance channels), which have a prolonged mean open time and low conductance.…”
Section: Postsynaptic Potentiation Effect Of Atpmentioning
confidence: 99%
“…Developmental changes of acetylcholine (ACh) receptor channels have been studied extensively in Xenopus myotomal muscle cells in vitro (Kidokoro, Brehm & Gruener, 1982; Brehm, Kidokoro & Moody-Corbett, 1984 a;Igusa & Kidokoro, 1987; Leonard, Nakajima, Nakajima & Carlson, 1988) as well as in vivo (Kullberg, Brehm & Steinbach, 1981;Brehm, Kullberg & Moody-Corbett, 1984b; Owens & Kullberg, 1989). Shortly after initial insertion of ACh receptor channels a great majority of channels are an embryonic type which have a prolonged mean burst duration.…”
Section: Introductionmentioning
confidence: 99%